Knowledge, Information and Creativity Support Systems Selected Papers from KICSS'2014 - 9th International Conference, held in Limassol, Cyprus, on November 6-8, 2014 - Kunifuji, Susumu; Papadopoulos, George Angelos; Skulimowski, Andrzej M.J; Kacprzyk , Janusz (Advances in Intelligent Systems and Computing,, 2016)
This volume consists of a number of selected papers that were presented at the 9th International Conference on Knowledge, Information and Creativity Support Systems (KICSS 2014) in Limassol, Cyprus, after they were substantially revised and extended. The 27 regular papers and 19 short papers included in this proceedings cover all aspects of knowledge management, knowledge engineering, intelligent information systems, and creativity in an information technology context, including computational creativity and its cognitive and collaborative aspects. .